VIDEO DOKUMENTER WISATA KABUPATEN DHARMASRAYA - Sindi Septiani; hendra afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The design of a tourist documentary video for Dharmasraya Regency, West Sumatra Province, aims to increase the number of visitors who are still small due to the ineffective use of promotional media. The author is interested in raising this problem and designing a final work entitled "Tourism Documentary Video of Dharmasraya Regency".The design method used in designing this documentary video is the Thiagarajan method called 4D with 4 stages consisting of Define, Design, Development, and Dissemination. The design of a tourist documentary video for Dharmasraya district uses the SWOT analysis method.The results of designing a tourist documentary video for Dharmasraya district are packaged in the form of a video in the MP4 Full HD format which is burned to a DVD disc, and promoted on a YouTube account and also broadcast on I NewS TV Padang. The supporting media chosen were DVD labels, DVD disc covers, t-shirts, posters, key chains, pins, tote bags and social media profile icons.Keywords: audio-visual media, natural tourism, historical tourism, padangroco temple, Dharmasraya regency tourism.